2013
DOI: 10.4028/www.scientific.net/amm.393.29
|View full text |Cite
|
Sign up to set email alerts
|

Green Lean TQM Suppliers, Organization and Customers Management Practices in Malaysian Automotive Companies

Abstract: Green Lean Total Quality (GLTQ) Suppliers, Organization and Customers Management System (SOCM) is a system comprises the interrelated linkages between suppliers; organization and customers in Environmental Management System (EMS) practices which are integrated to TQM with Lean Manufacturing (LM) principles. SOCM is essential especially in dealing with inefficient suppliers chain and customers management. The ultimate goal of this system is to focus on achieving total SOCM efficiency that uses EMS and Lean TQM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Verrier et al [14] found that linking the organization's performance with sustainable development is a platform for adding social (human) and environmental (green) dimensions to lean activities. The study by Azlina et al [15] established a framework model for Green Lean human resources management practices in the context of quality management. The main goal of the proposed system is to focus on achieving the full development of human resources oriented on their motivation and creativity to be part of a green and lean organization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Verrier et al [14] found that linking the organization's performance with sustainable development is a platform for adding social (human) and environmental (green) dimensions to lean activities. The study by Azlina et al [15] established a framework model for Green Lean human resources management practices in the context of quality management. The main goal of the proposed system is to focus on achieving the full development of human resources oriented on their motivation and creativity to be part of a green and lean organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…14 Employees' all ideas and initiatives are recorded in the information system of the organization, and those that meet the relevant criteria are considered. 15 Employees are aware of the environmental impact of the organization's operations, processes and technologies used. 16 Employees' absence is caused only by non-occupational diseases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainability research in automotive industry is central for the manufacturing management in exploring its drivers and barriers (Amrina & Yusof, 2012), lean manufacturing implementation (Azlina, Salleh, Kasolang, & Jaffar, 2011), performance indication (E. Amrina & Yusof, 2011) and green practices (Conding, Mohd Zubir, Hashim, Sri Lanang, & Habidin, 2012). In contrast, literature found that, in the new product development areas is limited on the eco design implementation (Taha, Sakundarini, Ariffin, Ghazila, & Gonzales, 2010) and increasing research demand on how companies successfully managed www.ccsenet.org/ass Asian Social Science Vol.…”
mentioning
confidence: 99%